Mechanical and Durability Properties of Foamed Concrete with the Addition of Oil Palm Trunk Fibre - Othuman Mydin, Md Azree (International Journal of Sustainable Construction Engineering and Technology, 2022)
Nowadays, in Malaysia, one of the country's challenges is the improper management and disposal of solid waste. The leading sector that generates most of the solid waste in Malaysia is the agricultural sector from oil palm fibre, similar to oil palm trunk fibre, which is also be used as an additive in producing foamed concrete (FC). However, FC presents a weakness in tension, which can be reduced by adding an adequate volume of waste biomass by-product such as oil palm trunk (OPT) fibre. Accordingly, this study was undertaken to investigate the potential of utilising OPT fibre as a reinforcement in FC. There were four different volume fractions of OPT fibre: 0.15%, 0.30%, 0.45%, and 0.60% used as an additive to the FC mix. Two densities, 600 kg/m3 and 1200 kg/m3, were cast and tested. All FC specimens were then prepared and left to cure and exposed to the elements for 7, 28, and 56 days. In this study, to properties were examined: mechanical and durability properties. The results showed that the addition of OPT fibre in FC improved the compressive strength, flexural strength, tensile strength, water absorption, drying shrinkage, porosity and ultrasonic pulse velocity of the FC. OPT's surface roughness was proved beneficial for fibre to matrix interfacial bonding since a coarser surface permits OPT fibre and matrix interlocking in the hardened cement matrix. Based on the results of this study for 600 kg/m3 density, 0.30% volume fraction was the optimum amount added to the FC to achieve the best durability and mechanical properties. While for 1200 kg/m3, 0.45% volume fraction of OPT was the optimum percentage.